Physico-Chemical Comparison of Different Tanks ofEffluent Treatment Plant of Dairy Waste - Gaur Mishra*, Arpana; Joshi, Smita (Asian Journal of Chemistry, 2010)
Dairy wastes are quite rich in degradable organic matter and exert a high oxygen demand. Waste water from dairy waste normally includes substantial concentration of fats, milk, proteins, lactose, minerals, detergents and sanitizers. The effluent of dairy waste is acidic due to conversion of lactose to lactic acid. this waste water can be treated by conventional and biological methods. Degree of treatment of dairy waste depends on its final mode of disposal. The treatment of dairy waste is quite essential from legislation and pollution point of view.